PRELIMINARY FINDINGS AND AWARENESS FROM THE C6-1 ARCHAEOLOGICAL EXPLORATION IN KRONGNO, DAKNONG PROVINCE - Lê Xuân Hưng; La Thế Phúc; Phạm Thị Phương Thảo; Vũ Tiến Đức; Nguyễn Trung Minh (Tạp chí Khoa học Đại học Đà Lạt)
The volcanic cave system in Krongno district is not only of geological interest, but it also possesses unique ecological and cultural value. Vietnamese archaeologists have discovered and studied over 200 limestone caves with prehistoric dwellings dating from the early period of the Old Stone Age to the New Stone Age. However, the traces of prehistoric people residing in the Krongno volcanic cave (Daknong) are the first to be discovered in a volcanic cave in Southeast Asia. This paper presents the preliminary findings regarding the discovery of dwellings and stone tool processing of prehistoric people living around 6,000 – 4,000 years ago obtained from the investigation of 10 caves and the excavation of the C6-1 volcanic cave in Krongno in 2017. These findings positively contribute to the study of the cultural history of prehistoric communities in Daknong province, in particular, and the Central Highlands in general. In addition, the research contributes to the construction of the "Krongno Volcanic Geopark” and the preservation and promotion of archaeological heritage as well as the socio-economic development of Daknong province.